Mammary Tumorigenesis and Metabolome in Male Adipose Specific Monocyte Chemotactic Protein-1 Deficient MMTV-PyMT Mice Fed a High-Fat Diet - Yan, Lin; Sundaram, Sneha; Rust, Bret M.; Picklo, Matthew J.; Bukowski, Michael R. (Frontiers in Oncology, 2021)
Male breast cancer, while uncommon, is a highly malignant disease. Monocyte chemotactic protein-1 (MCP-1) is an adipokine; its concentration in adipose tissue is elevated in obesity. This study tested the hypothesis that adipose-derived MCP-1 contributes to male breast cancer. In a 2x2 design, male MMTV-PyMT mice with or without adipose-specific Mcp-1 knockout [designated as Mcp-1-/- or wild-type (WT)] were fed the AIN93G standard diet or a high-fat diet (HFD) for 25 weeks. Mcp-1-/- mice had lower adipose Mcp-1 expression than WT mice. Adipose Mcp-1 deficiency reduced plasma concentrations of MCP-1 in mice fed the HFD compared to their WT counterparts. Mcp-1-/- mice had a longer tumor latency (25.2 weeks vs. 18.0 weeks) and lower tumor incidence (19% vs. 56%), tumor progression (2317% vs. 4792%), and tumor weight (0.23 g vs. 0.64 g) than WT mice. Plasma metabolomics analysis identified 56 metabolites that differed among the four dietary groups, including 22 differed between Mcp-1-/- and WT mice. Pathway and network analyses along with discriminant analysis showed that pathways of amino acid and carbohydrate metabolisms are the most disturbed in MMTV-PyMT mice. In conclusion, adipose-derived MCP-1 contributes to mammary tumorigenesis in male MMTV-PyMT. The potential involvement of adipose-derived MCP-1 in metabolomics warrants further investigation on its role in causal relationships between cancer metabolism and mammary tumorigenesis in this male MMTV-PyMT model.